Low carbon energy transitions for informal settlements: a case study of iShack South Africa - Glasser, Zachariah (Department of Environmental and Geographical Science, 2018)
The majority of informal settlements in South Africa do not have access to reliable, safe, and clean energy. Infrastructural constraints, poor service delivery, the inapt application of policy, and the financial constraints of those living in informal settlements all contribute towards this problem of energy poverty. This dissertation argues that low carbon energy transitions, such as solar home systems, are a viable means for overcoming issues of energy poverty in informal settlements. This dissertation examines the role of urban experimentation in implementing low carbon energy transitions within informal settlements in South Africa, through exploring interactions between policy, technology and justice. The iShack Project (improved Shack) is used as a case study, to identify, analyse, and discuss the ways in which solar home systems have resulted in social and financial changes amongst the residents in Enkanini, Stellenbosch. These relate to changing fuel use patterns, reducing shack fire risk and addressing issues of access and affordability. Multilevel perspective (MLP) and the political ecology approach are the two analytical tools used to discuss the broader conditions that give rise to transitions, as well as providing a more in-depth look at the experiences of those making up the 'social' aspect of socio-technical transitions. These analytical tools informed a series of interviews, which is the primary method through which data was gathered, by highlighting prominent components of agency and power - providing greater understanding of the lived realities of the Enkanini residents. The interviewing process provided an opportunity for residents of Enkanini to voice their opinions on this urban experiment and discuss the impact iShack has had on their lives. Photographs accompany many of the findings in this dissertation and provide a valuable lens through which the lived reality of the Enkanini residents can be more accurately represented. Using the case study of the iShack Project in Enkanini, the findings of this dissertation highlight that policy, technology and justice come to positively reinforce one another in addressing the issue of energy poverty in South Africa. For example, the granting of the Free Basic Electricity (FBE) subsidy to the iShack Project has made it possible for the intermediary to address justice issues, such as the poor being able to access and afford reliable, safe, and clean electricity. Furthermore, iShack's technological innovations, such as "Flash" and the "Flash wallet" have brought about foundational changes in some values, goals, operational procedures and decision-making processes taking place in the community - especially around the notion of monetary savings. This also points to the fact that these technological innovations are physical manifestations of policy itself. The findings show that low carbon energy transitions can be a viable means of overcoming energy poverty in informal settlements and addressing issues of access and affordability for the poor. However, local government plays an important role in being able to adapt local policy in such a way that it creates an enabling environment for an intermediary to be supported or strengthened in this.